Hungarian Monitoring, 4 July 1990 . [Magyar rádiófigyelő], 1990. július 4 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Brussels conference on supporting Eastern European countries - Split expected within CPSU - Interior Ministry scandal in Poland Domestic Affairs: - Referendum announced on presidential elections - Nationalist provocations in Romania - Bolya Lyceum, Hungarian-language school in Targu Mures, to become independent - On the consequences of amnesty - Albanian refugees in Budapest Economy: - Self-liquidation at the Dorog Coalmine - Bush opposes support for the Soviet Union Külpolitika: - Brüsszeli konferencia Kelet-Európa országainak támogatásáról - Várható a szakadás az SZKP-n belül - BM-botrány Lengyelországban Belpolitika: - Népszavazás kiírása a köztársasági elnök megválasztásáról - Nacionalista provokátorok Romániában - Önállósul a Bolyai Líceum - Az amnesztia következményeiről - Tiranai menekültek Budapesten Gazdaság: - Önfelszámolás a dorogi szénbányánál - Bush ellenzi a Szovjetunió megsegítését